Patent Litigation with Endogenous Disputes - Bessen, James E; Meurer, Michael J (American Economic Review, 2006)
The recent explosion of patenting and patent disputes has sparked a growing literature on the economics of patent litigation. Generally, models in this literature take the existence of a dispute as given. This assumption is troubling because it hampers the interpretation of empirical studies of patent litigation and the assessment of many patent policy reforms. Disputes would not arise if all technology adopters obtained ex ante licenses from patent owners. This suggests that two stories could explain the origin of patent disputes. In one, the technology adopter observes a patented technology, but chooses to imitate, “inventing around” and/or hiding the infringement. In the other, the adopter develops his own technology and is unaware of another firm’s putative patent rights. This kind of innocent infringement occurs because patent rights often have uncertain boundaries or questionable validity. In addition, the sheer number of patents facing a typical innovator makes careful assessment quite burdensome. Furthermore, patent claims are often hidden (sometimes strategically) until after firms have made technology investments. These two accounts suggest that a model of disputes should consider the decisions of patent owners to invent, to patent, and to monitor use of the patented technology by others; and the decisions of potential infringers to monitor extant patents, and develop and adopt new technology. Claude Crampes and Corinne Langinier (2002) endogenize disputes by focusing on a patent owner’s monitoring activity and imitative behavior by potential infringers. Our model includes this behavior, but it also includes defendants who “invent around” a patent, and defendants who are unaware of the patented technology. We find that this richer model generates testable implications that better match empirical evidence on patent litigation.